Kemmy Exports a methods study - Mag-iba, Arlene; Maravillas, Ma. Carmela; Navarro, Marilyn Anne.; Paragas, Edgar; Ventura, Raymundo (Diliman, Quezon City College of Engineering, 1990)
The project study has two major areas of concern : the method study and the work measurement. Both areas have been closely studied and the group has come up with several recommendations. Perhaps due to the fact that the project site is relatively new, the group has noted several improvements needed with regards to the different aspects of the production process. Method Study : Method study deals with the analysis of both the factory layout, which concerns the entire production process, and the workplace layout, which concerns the specific operation under study chosen by the group. The first layout involves movement of workers in the work area and the flow and handling of materials. The group has noted several recommendations which can very well improve the existing conditions in the factory. In the plant layout alone, the group has noted some idle spaces which may be used productively. The movement of workers and consequently the transport of materials from one work area to another is much easier and smooth if some organized and effective division of the entire work place is accomplished. The second layout involves working conditions and environment, jigs and fixtures, and some ergonomic considerations. The group believes that certain renovations are necessary to improve working conditions in the factory so as to maximize production output and to develop better working habits among the workers. Work Measurement : Work measurement deals with the time study of the present method employed by the factory. This involves the determination of how long it would take to accomplish one operation. In our case, we used the sanding operation in our stop-watch studies. We took random observations of the time it takes to sand one pole. From these observations, we determined the basic time. After analyzing the present method, we eliminated certain elements of the operation so as to shorten the operation time without sacrificing the quality of the finished product. These recommendations are further discussed in our study of the alternative method which is recommended by the group.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Kemmy Exports; Furniture industry and trade; Systems analysis